Tetanus Toxoid Vaccination Coverage Among Women of Reproductive Age: Experience From a Rural Community (Bangladesh Medical Journal, 2014)
Tetanus Toxoid (TT) is a routine vaccination activity under Expanded Program on Immunization (EPI) in Bangladesh. The women of reproductive age (15-49 years) are the target population for five doses of TT vaccine to protect them from tetanus. The study was a cross-sectional study in context of a rural community. The study was conducted to assess TT vaccination coverage among the women of reproductive age in a rural community of Bangladesh. A total of 224 women of reproductive age were randomly included in the study following selection criteria. Data was collected by recall history and reviewing immunization card by using a semi-structured questionnaire and checklist respectively. Data was processed and analyzed considering both descriptive and inferential statistics. Mean age of the women was 27.22 ± 6.87 years and major part (30.4%) was illiterate. Most of the women were married (87.6%) and housewives (81.3%). Mean age at marriage was 17+2.37 years and mean age at first child birth was 18+2.24 years. On the basis of recall history and vaccination card, 83.5% women received first dose of TT (TT1), while 16.5% didn't receive any TT vaccine. Among the women received all five doses of TT, 'Crude Vaccination Rate" was 37.0% and ''Valid Vaccination Rate' was 33.0%. By card, these rates were 18.5% and 14.2% respectively. The invalid doses found 6.2% for TT2, 7.3% for TT3, 12.5% for TT4 and the lowest 10.8% for TT5 dose. The dropout rate was 5.3% for TT1-TT2, 14.7% for TT2-TT3, the highest 31.1% for TT3-TT4 and 20.2% for TT4-TT5 while 55.6% was for TT1-TT5. Vaccination coverage was significantly higher among the women aged 25-29 years (91.0%) and having HSC level education (92.3%) (x2 test, p